Technologies for urban and spatial planning virtual cities and territories - Pinto, Nuno Norte, 1979- (Advances in civil and industrial engineering (ACIE) book series ;, 2014)
"This book covers a multitude of newly developed hardware and software technology advancements in urban and spatial planning and architecture, drawing on the most current research and studies of field practitioners who offer solutions and recommendations for further growth, specifically in urban and spatial developments"--